Dyslipidemia alters sperm maturation and capacitation in LXR-null mice. Issue 6 (December 2017) - Whitfield, M; Guiton, R; Rispal, J; Acar, N; Kocer, A; Drevet, J R; Saez, F
Abstract : Lipid metabolism disorders (dyslipidemia) are causes of male infertility, but little is known about their impact on male gametes when considering post-testicular maturation events, given that studies concentrate most often on endocrine dysfunctions and testicular consequences. In this study, three-month-old wild-type ( wt ) and Liver-X-Receptors knock out ( Lxrα;β − / − ) males were fed four weeks with a control or a lipid-enriched diet containing 1.25% cholesterol (high cholesterol diet (HCD)). The HCD triggered a dyslipidemia leading to sperm post-testicular alterations and infertility. Sperm lipids were analyzed by LC–MS and those from Lxrα;β − / − males fed the HCD showed higher chol/PL and PC/PE ratios compared to wt -HCD ( P  < 0.05) and lower oxysterol contents compared to wt ( P  < 0.05) or Lxrα;β − / − ( P  < 0.05). These modifications impaired membrane-associated events triggering the tyrosine phosphorylation normally occurring during the capacitation process, as shown by phosphotyrosine Western blots. Using flow cytometry, we showed that a smaller subpopulation of spermatozoa from Lxrα;β − / − -HCD males could raise their membrane fluidity during capacitation ( P  < 0.05 vs wt or wt-HCD ) as well as their intracellular calcium concentration ( P  < 0.05 vs Lxrα;β − / − and P  < 0.001 vs wt ). The accumulation of the major sperm calcium efflux pump (PMCA4) was decreased in Lxrα;β − / − males fed the HCD ( P  < 0.05 vs Lxrα;β − / − and P  < 0.001 vs wt ). This study is the first showing an impact of dyslipidemia on post-testicular sperm maturation with consequences on the capacitation signaling cascade. It may lead to the identification of fertility prognostic markers in this pathophysiological situation, which could help clinicians to better understand male infertilities which are thus far classified as idiopathic.